2002
DOI: 10.1097/00004424-200207000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Inhibits Proliferation of Cell Lines Responsible for Metal Stent Obstruction:

Abstract: Paclitaxel incubation resulted in a dose dependent inhibition of cell proliferation of human epithelial gallbladder cells, human fibroblasts and pancreatic carcinoma cells. This inhibitory effect of paclitaxel on the cell lines could serve as the basis to develop drug coated or drug eluting stents for malignant biliary strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 26 publications
0
30
0
3
Order By: Relevance
“…1 Paclitaxel, a chemotherapeutic agent that has been shown to inhibit cell proliferation in fibroblasts, pancreatic cancer, and epithelial cells in the gallbladder, has been studied for its effect on patency. 33 Suk et al investigated Niti-S Mira-Cover stents coated with paclitaxel. They inserted 21 stents in patients diagnosed with unresectable malignant biliary obstruction.…”
Section: Drug-eluting Stentsmentioning
confidence: 99%
“…1 Paclitaxel, a chemotherapeutic agent that has been shown to inhibit cell proliferation in fibroblasts, pancreatic cancer, and epithelial cells in the gallbladder, has been studied for its effect on patency. 33 Suk et al investigated Niti-S Mira-Cover stents coated with paclitaxel. They inserted 21 stents in patients diagnosed with unresectable malignant biliary obstruction.…”
Section: Drug-eluting Stentsmentioning
confidence: 99%
“…36 In vitro and in vivo studies (the latter using drug-coated SEMSs) have demonstrated that local exposure to paclitaxel, 5-fluorouracil, and gemcitabine can induce local responses when placed in contact with both benign and malignant GI tract tissues. [37][38][39][40][41][42][43][44] To date, there are only a few small published case series in humans. These demonstrated that partial responses in unresectable cholangiocarcinoma can be achieved with a carboplatincoated percutaneous biliary tube, 45 and endoscopically placed drug-eluting SEMS may be associated with improved stent patency and overall survival in patients with extrahepatic cholangiocarcinoma.…”
Section: Drug-eluting Stents In the Gi Tractmentioning
confidence: 99%
“…Anti-tumor agents are usually delivered by simple diffusion, into the mucosal and submucosal layers. The recently introduced paclitaxel-eluting covered metal stents may prevent occlusion from tumor ingrowth by the anti-tumor effect of paclitaxel [31]. These stents were reported to be safe and effective in animal and human studies [32,33].…”
Section: Update In Palliation Of Biliary Tumorsmentioning
confidence: 99%